2019
DOI: 10.1101/792846
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expression profiling of single cells and patient cohorts identifies multiple immunosuppressive pathways and an altered NK cell phenotype in glioblastoma

Abstract: Glioblastoma (GBM) is an aggressive cancer with a very poor prognosis. Generally viewed as weakly immunogenic, GBM responds poorly to current immunotherapies. To better understand this problem we used a combination of NK cell functional assays together with gene and protein expression profiling to define the NK cell response to GBM and explore immunosuppression in the GBM microenvironment.In addition, we used transcriptome data from patient cohorts to classify GBM according to immunological profiles. We show t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Since the above results are consistent with IL-33-expressing GBM recruiting peripheral immune cells, we extended the characterization of CD45 + immune cells using single-cell RNA sequencing (scRNAseq). To maintain focus on the innate immune cell repertoire, we chose to perform these studies in IL-33 + and IL-33 − xenografts, a model that allows assessment of the differences in activation states within the tumor immune repertoire, as well as the recruited innate immune cells, such as monocytes and NK cells are reported to be enriched within a glioma tumor environment [91][92][93][94][95] . Cerebral leukocytes were isolated as described above from IL-33 + and IL-33 − tumorbearing hemispheres, sorted for CD45, and RNA sequenced using the 10× Chromium platform.…”
Section: Controlmentioning
confidence: 99%
“…Since the above results are consistent with IL-33-expressing GBM recruiting peripheral immune cells, we extended the characterization of CD45 + immune cells using single-cell RNA sequencing (scRNAseq). To maintain focus on the innate immune cell repertoire, we chose to perform these studies in IL-33 + and IL-33 − xenografts, a model that allows assessment of the differences in activation states within the tumor immune repertoire, as well as the recruited innate immune cells, such as monocytes and NK cells are reported to be enriched within a glioma tumor environment [91][92][93][94][95] . Cerebral leukocytes were isolated as described above from IL-33 + and IL-33 − tumorbearing hemispheres, sorted for CD45, and RNA sequenced using the 10× Chromium platform.…”
Section: Controlmentioning
confidence: 99%
“…Alternative stratification of GBM based on consensus immunome clusters (CIC) identified two immunologically active GBM clusters ( 32 ). These clusters expressed genes associated with cytotoxic T lymphocyte (CTLs) and NK cell activation, such as granzyme B ( GZMB ) and interferon gamma ( IFNG ), and genes linked to feedback inhibitory mechanisms including FOXP3 , immune checkpoint inhibitors ( CTLA-4, PD-1, TIM3, VISTA ) and their ligands e.g.…”
Section: Glioblastoma (Gbm) Subtypes and Their Associated Immune Landmentioning
confidence: 99%
“…These clusters expressed genes associated with cytotoxic T lymphocyte (CTLs) and NK cell activation, such as granzyme B ( GZMB ) and interferon gamma ( IFNG ), and genes linked to feedback inhibitory mechanisms including FOXP3 , immune checkpoint inhibitors ( CTLA-4, PD-1, TIM3, VISTA ) and their ligands e.g. PD-L1 and galectin-9 ( 32 ). Nevertheless, these CICs did not discriminate patients with respect to survival outcome, potentially due to the low frequencies of CTLs and NKs and the strong immunosuppressive environment mediated by the myeloid compartment.…”
Section: Glioblastoma (Gbm) Subtypes and Their Associated Immune Landmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, GSCs secrete periostin (POSTN), which recruits M2-like tumor-associated macrophages (TAMs) and promotes GBM aggressiveness [ 234 ]. Others reported that GSCs express multiple immunomodulatory cell-surface molecules [ 235 ], including GM-CSF, that induce TAMs development by promoting the survival and differentiation of bone-marrow-derived monocytes [ 236 ]. Furthermore, GSCs are reported to downregulate the expression of histocompatibility complex Class I (MHC-I) molecules and antigen-processing machinery (APM) components when compared to non-GSCs, by overactivating the WNT pathway [ 135 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%